2000
DOI: 10.1159/000045560
|View full text |Cite
|
Sign up to set email alerts
|

No Association between Deletion-Type Angiotensin-Converting Enzyme Gene Polymorphism and Left-Ventricular Hypertrophy in Hemodialysis Patients

Abstract: Left-ventricular hypertrophy (LVH), a bad prognostic sign, is a common finding in hemodialysis patients. The aim of the study was to analyze factors, including angiotensin-converting enzyme (ACE) genotype that may have an effect on the development of LVH in hemodialysis patients. Seventy-nine hemodialysis patients (42 males, 37 females, mean age 37.7 ± 13.1 years) and 82 age- and sex-matched normotensive healthy controls (40 males, 42 females, mean age 35.6 ± 5.7 years) were included. Left-ventricular mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
4
2
Order By: Relevance
“…While the increased D allele frequencies in the hypertension patients were reported by several studies (11,14,(22)(23)(24)(25)(26), no differences in the D and I allele frequencies were determined by other investigations (27)(28)(29)(30)(31)(32)(33), being in agreement with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…While the increased D allele frequencies in the hypertension patients were reported by several studies (11,14,(22)(23)(24)(25)(26), no differences in the D and I allele frequencies were determined by other investigations (27)(28)(29)(30)(31)(32)(33), being in agreement with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The association of ACE genotype and eNOS genotype with CVD in patients on hemodialysis remains controversial [9, 10, 11, 12]. In the present cross-sectional study, there was no significant difference in the distributions of the ACE genotype and the eNOS genotype between patients with a CVD history and patients without a CVD history.…”
Section: Discussioncontrasting
confidence: 57%
“…Recently, Aucella et al [10]have demonstrated that frequencies of the ACE DD genotype are similar in uremics and in controls, suggesting that ACE I/D polymorphism may influence CVD. However, Yildiz et al [11]have reported that the ACE DD genotype has no effect on LVH in hemodialysis patients. On the other hand, Yokoyama et al [12]have reported that the eNOS a/b polymorphism may have some relation to the severity of renal anemia.…”
Section: Introductionmentioning
confidence: 99%
“…Left ventricular hypertrophy (LVH), a major independent risk factor for cardiovascular morbidity and mortality, is a common finding in hemodialysis patients [1]. In dialysis patients, ventricular hypertrophy, interstitial myocardial fibrosis, and endothelial dysfunction, which all limit the coronary flow reserve available to the myocardium during stress and which are frequent findings in ESRD, may play a pathophysiological role.…”
Section: Introductionmentioning
confidence: 99%